ORAL HEALTH STATUS OF CHALDREN WITH INFECTIOUS MONONUCLEOSIS IN THE PAST MEDICAL HISTORY - N.L. Chukhray; S.V. Savchyn (Український стоматологічний альманах)
Dental caries and periodontal tissue diseases remain one of the most actual problems in pediatric dentistry. There is also a trend towards an increase in the prevalence of malocclusion. Dental morbidity in children in most cases develops under the influence of both local and general factors. Somatic pathology has a particularly significant impact on the development of dental morbidity in children, caused by metabolic disorders, which serves as the pathogenetic basis for the development of diseases. Viral infection, which is widespread among children and adults, plays a significant role in the development of dental diseases. In recent years, there has been an increase in the incidence of children with infectious mononucleosis caused by Epstein-Barr virus. Therefore, the assessment of oral health status in children with infectious mononucleosis will allow the development of effective means of preventing and treating diseases.